Using step activity monitoring to assess ambulatory activity before and after total ankle arthroplasty - Che Ahmad, Aminudin; Lacrazl, A.; Crevoisier, X,; Courvoisier, D.; Assal, M. (E M H Schweizerischer Aerzteverlag AG, 2009)
Introduction: The aim of this study is to compare the walking activity of a cohort of individuals before and after total ankle arthroplasty (TAA). Methods: Nineteen consecutive patients (ten males and nine females) with mean age of 58.72, selected for TAA between January and June 2006, were prospectively reviewed with the use of a dedicated ambulatory activity-monitoring device to assess their natural ambulatory activity. Patients were tested in the community for two weeks duration, one month prior to and at least eighteen months after surgery. The ambulatory parameters were assessed through measurement of the number of steps at different cadence, and the time spent walking at different walking paces. Data were analyzed by using specific statistical methods. Results: This study revealed a significant improvement in the number of steps walked at normal cadence (b = 331.63, p = .00) and significantly reduced at low cadence (b = –402.52, p = .00) and medium cadence (b = –386.29, p = .00), before and after TAA. However, there are no significant different between two phases of assessment in term of time spent walking. Conclusion: These quantitative data allow a clear comparative assessment of walking ability following TAR and demonstrates that this intervention improves patient’s walking pace.